Restorative justice in the child justice system: implementation in other jurisdictions - Ab Aziz, Norjihan; Hussin, Nasimah; Mohamed, Nurah Sabahiah; Samsudin, Najaa Syahirah (Secholian Publication, 2022)
Developments in the child criminal justice system internationally, indicate that restorative justice has been adopted as one of the mechanisms of resolving criminal cases. Some countries, such as the United Kingdom and New Zealand integrate restorative justice process into the child justice system to complement the available law in dealing with child offenders. It can be regarded asan alternative or complementary to the child justice system that allows the perpetrator and the victim to resolve the criminal dispute based on their needs and interests with the assistance of a neutral third party. Unless the discussion or agreement is unable to reach, the case will be forwarded to the court that has jurisdiction to hear and determine the case. However, Malaysia does not have specific provisions in the law that allow criminal offences committed by a child to be resolved through restorative justice. Thus, this article examines the concept of restorative justice and its implementation in the child criminal justice system in New Zealand and the United Kingdom. This article also examines Malaysian position on restorative justice for child offenders and how it can be integrated into the Malaysian child justice system. It is proposed that the Child Act 2001 be amended so that restorative justice can be introduced and implemented as part of the child justice system in Malaysia. This article adoptsqualitative research with reference to printed and online materials such as books, journal articles, acts, and decided cases that are available in the library and the internet